140. Enterococcus faecalis CL Synthases Have Redundant Roles and Play A Major Role in Phospholipid Redistribution Associated with Daptomycin Resistance. (15th December 2022) - Nguyen, April; Polamraju, Vinathi; Zhang, Rutan; Panesso, Diana; Khan, Ayesha; Mileykovskaya, Eugenia; Cecilia Tran, Truc; Xu, Libin; Vitrac, Heidi; Arias, Cesar A
Abstract: Background: Daptomycin (DAP) is a lipopeptide antibiotic targeting membrane anionic phospholipids (APLs) at the division septum. DAP resistance (DAP-R) has been associated with activation of the LiaFSR system resulting in redistribution of APL microdomains (likely containing cardiolipin, CL) away from the septum. E. faecalis ( Efs ) possess two CL synthase genes, ( cls1 and cls2 ) and changes in Cls1 are associated with DAP-R. However, the roles of each enzyme are unknown. Here, we characterize the roles of cls genes in DAP-R in the context of LiaFSR activation. Methods: cls1 and/or cls2 were deleted from Efs OG117 and OG117Δ liaX (DAP-R strain with an activated LiaFSR response). qRT-PCR was used to study gene expression of cls1 and cls2 in the cls mutants. Membrane lipid content was analyzed using hydrophilic interaction chromatography-mass spectrometry. Mutants were characterized by DAP minimum inhibitory concentration (MIC) using E-test and localization of APL microdomains with 10-N-nonyl-acridine orange. Results: cls1 and cls2 are upregulated in exponential phase of DAP-R Efs OG117Δ liaX relative to DAP-S Efs OG117, with only cls1 upregulated in stationary phase. Deletion of cls1 or cls2 resulted in upregulation of the other cls gene, independent of activation of LiaFSR. Lipidomics analysis confirmed that deletion of both cls resulted in complete absence of cell membrane CL content. When comparing CL profiles of Δcls1 relative to Δcls2 in both DAP-S and DAP-R, both strains produced similar levels and species of CL. However, development of DAP-R caused a change in membrane lipid content, namely, an increase in CL with no significant difference in phosphatidylglycerol compared to DAP-S strain. Evaluation of CL species in DAP-R shows a shift towards species containing longer fatty acid chains and higher saturation. Independent deletions of cls1 or cls2 did not revert the DAP phenotype. In contrast, deletion of both cls genes decreased the DAP MIC (2-3 fold) relative to the parent strain and restored septal localization of APL microdomains. DAP MIC was restored upon trans complementation of either cls1 or cls2 into the double deletion mutant. Conclusion: Our results support a major role of Cls in changes in cell membrane architecture and DAP-R in enterococci, with overlapping roles for Cls1 and Cls2. Disclosures: Cesar A. Arias, MD, PhD, Entasis Phramceuticals: Grant/Research Support|MeMed Diagnostics: Grant/Research Support|Merck: Grant/Research Support.